The Strategic Training And Development: Integration And Contingency For High Quality - Halim, M (Revenue: Lentera Bisnis Manajemen, 2023)
This piece of research is referred to as "Strategic Training and Development: Integration and Contingency for High Quality." In the context of training and development (T&D) for employees, the goals of this study were to provide an overview of the process of strategy formulation, an overview of the process of strategy implementation, an account of the process of strategy evaluation, and an overview of how to measure the success of the implementation. The qualitative research approaches were applied in this case study. Interviews, observations, and documentation were the three methods that were used to collect data. The key sources of information consisted of six different supervisors and staff. The data were analyzed using analyses performed both before and during the fieldwork. The validity test was conducted by combining the credibility test with the transferability test. According to the findings of this study, the process of formulating a strategy in T&D is characterized by the following: the relationship between strategic objectives and the organization's mission; the needs assessments conducted by the department; guest opinions; government regulation or policy action; and financial and budgetary concerns. The description of the implementation strategy in T&D was a cross-hierarchy task that required the performance of a series of processes, including program development, budgeting, and the procedure to follow the organization's strategies that had been designed to achieve synergy. The T&D strategy detailed an evaluation procedure that included evaluating the field performance of the company, customer input, and revenue from the company's products and services. The T&D approach is stated as a success indication of increased revenue, satisfied customers, and a reduction in negative feedback.